2016
DOI: 10.1002/ase.1659
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of outcomes following the replacement of traditional histology laboratories with self‐study modules

Abstract: Changes in medical school curricula often require educators to develop teaching strategies that decrease contact hours while maintaining effective pedagogical methods. When faced with this challenge, faculty at the University of Cincinnati College of Medicine converted the majority of in-person histology laboratory sessions to self-study modules that utilize multiple audiovisual modalities and a virtual microscope platform. Outcomes related to this shift were investigated through performance on in-house examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…The most common change has been the transition from a numerical or letter grade hierarchical system to a simple pass/fail grading system for preclinical courses (Bloodgood et al, ; Reed et al, ). In certain institutions, contact hours have also been reduced (Slavin et al, ; Thompson and Lowrie, ), and unnecessary details have been eliminated in the early stage of the program (Aboul‐Fotouh and Asghar‐Ali, ; Slavin et al, ). These changes have been bolstered by the introduction of longer electives (Ames et al, ; Aronsson et al, ), and establishment of learning communities that allow students to focus more on material they have identified as being of greater long‐term value in their professional career (Carpenter et al, ; Ebert et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
“…The most common change has been the transition from a numerical or letter grade hierarchical system to a simple pass/fail grading system for preclinical courses (Bloodgood et al, ; Reed et al, ). In certain institutions, contact hours have also been reduced (Slavin et al, ; Thompson and Lowrie, ), and unnecessary details have been eliminated in the early stage of the program (Aboul‐Fotouh and Asghar‐Ali, ; Slavin et al, ). These changes have been bolstered by the introduction of longer electives (Ames et al, ; Aronsson et al, ), and establishment of learning communities that allow students to focus more on material they have identified as being of greater long‐term value in their professional career (Carpenter et al, ; Ebert et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
“…Perhaps adding a think‐aloud written or recorded narration of the expert’s thoughts provided in addition to the scan path could enhance the benefits of the feedforward training material of the present study. Narration could also increase the receptivity of the new training materials by students, as it has been indicated that instructor or expert narration is beneficial and desired by students when included in online self‐study modules (Thompson and Lowrie, ). Additionally, the use of think‐aloud narration could prevent novices from neglecting the global portion of the search.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐directed learning using a flipped classroom approach was utilized to instill student responsibility and enhance student motivation towards learning. Individual Portfolios were designed to promote self‐directed learning, which has been correlated with positive learning outcomes (Multon, et al, ; Thompson and Lowrie, ). Through self‐directed learning, students were better able to focus on content and concepts not yet mastered and less so on content and concepts already mastered.…”
Section: Discussionmentioning
confidence: 99%